Power relations in the wheat-to-bread commodity chain in South Africa - Joynt, Katherine (My University, 2019)
A familiar vision of the future of food holds that the worlds’ population will be fed sufficiently and sustainably through extraordinary productivity-enhancing innovation in technology and bioscience, combined with market efficiency in both financialised trade and global agricultural production. Although this vision is widely accepted by the public and adopted by development institutions and states, the findings of this study suggest that this account of market-led global development is an improbability. Rather, the actual effects of financialised neoliberal capitalism are contradictory and uneven. In this thesis I demonstrate how the reproduction and remaking of global power through both the real economy and financialisation has effects on local economic actors. This thesis uses a word-systems power resources approach to analyse of shifting power relations in the wheat to bread commodity chain in South Africa where industrial bread is a staple food for poor consumers. Typical of many chains in the global capitalist agro-food system, this commodity chain is characterised by vertical and horizontal consolidation in every node from seed to retail, and the increasing importance of finance actors. This thesis concretely demonstrates how the historically embedded oligopolistic power of large agribusiness, food processing corporates and retailers is maintained and expanded through particular governance strategies, innovation, and the use of economic, hegemonic and political influence. Furthered by increasing financialisation, these power relations and processes in the wheat to bread commodity chain impact on smaller economic actors, workers and consumers. This is done through the ‘squeezing’ of capitalist wheat farmers who also face severe ecological risks and constraints, the subsequent consolidation of wheat farms and the digitised mechanisation of the labour process, and the provision of a ‘cheap’ and unhealthy staple food for poor consumers. The shrinking wheat industry in South Africa is characterised by farmer debt, insolvency and the retreat of smaller-scale producers who tended to use more labour-intensive farming from wheat production, while the privitised wheat seed industry is now entering what seed breeders and wheat producers have termed a ‘crisis’. In turn, worker power is weakened through displacement on wheat farms due to mechanisation, and increasing precarity in the milling, baking and retail nodes of the chain. Households, to which workers and the unemployed belong, are faced with food insecurity which is exacerbated by the anti-competitive behaviour in food chains, with the price-fixing bread 4 cartel being just one example, and the volatile wheat prices which are reflected in the price of bread. This case study contributes to our understanding of the workings of the global agro-food system within which agrarian and food movements seek to create alternatives. It suggests that these movements must take seriously the contradictory role of the state as well as the pressure on agrarian capital in the context of global oligopolistic and hegemonic corporate and finance structures.
thesis submitted to the University of the Witwatersrand in fulfillment of the requirements of the degree of Doctor of Philosophy (Sociology), 2019